Development of Interactive Learning Media (MPI) to Improve Student Motivation and Learning Outcomes in Elementary School - Mamik Indrawati; Lilik Sri Hariani; Onik Farida Ni`matullah (STKIP Taman Siswa Bima, 2025)
This research aims to develop MPI Google Slides based Pear Deck to increase the motivation and learning outcomes of class VI students at SDN Muneng Leres II on the material Important Events Leading Up to the Proclamation of Indonesian Independence. The method used is research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) developed by Reiser and Mollenda. The subjects in this research were all class VI students at SDN Muneng Leres II for the 2024/2025 academic year, totaling 20 people, consisting of 11 male students and 9 female students. They also become test subjects in media development which is carried out through the stages of validation, implementation and evaluation of media effectiveness. Preliminary data obtained from diagnostic tests showed that only 35% of the 20 students had achieved an adequate level of understanding of the material, while the other 65% had not met the Learning Goal Achievement Criteria (KKTP). The research results show that the use of the developed MPI significantly increases students' understanding and learning motivation. Even though the correlation between pre-test and Post-test scores was weak, there was a significant increase in learning scores after the media intervention was implemented. Apart from cognitive improvements, students also show affective developments, such as increased interest, active involvement, self-confidence, and satisfaction in the learning process. This interactive media has proven effective in presenting historical material in an interesting, contextual and participatory manner. Thus, the development of MPI Google Slides based Pear Deck very relevant for enriching students' learning experiences in a comprehensive and meaningful way in social studies learning at the elementary school level.